Imagery and social representations of the Coronavirus pandemic in East African press: A critical content analysis of The East African newspaper - Kodak, Benard; Atieno Oduor, Juliet (International Journal of Scientific Research and Management (IJSRM), 2023)
The COVID-19 pandemic continues to be a phenomenon intersecting different parts of the world. The East African Community which prides itself for enabling socio-economic, political and cultural integration between its member states has had to deal with uncertainties caused by misinformation about the pandemic, which in turn threaten to derail its objectives. In line with this, The East African newspaper stands out as a leading provider of information concerning each of the countries in the community. And although a report in the MarketWatch (2023) indicates that the World Health Organization expects to declare end of the pandemic some time in 2023 as the virus has become more like seasonal flu, The East African newspaper which has established itself as a leading provider of information covering the five (5) member states of the East African Community has continually reported on the pandemic. How this publication represents the pandemic can influence how its readers understand it. Thus, guided by the Social Representation Theory (SRT) and employing a critical content analysis approach, this paper examines how the newspaper uses imagery in creating social representations about the pandemic. This study contributes to the discourse of media representations of pandemics.